Telepharmacy for outpatients with cancer: An implementation evaluation of videoconsults compared to telephone consults using the CFIR 2.0 - Marissa Ryan; Elizabeth C. Ward; Clare Burns; Christine Carrington; Katharine Cuff; Mhairi Mackinnon; Centaine L. Snoswell (Elsevier, 2024)
Background: Medication history telepharmacy consults are conducted prior to patients commencing their systemic anti-cancer therapy. At the study institution, this has historically been carried out as an unscheduled telephone consult. However, due to challenges with telephone consults, a scheduled videoconsult model was established. Funding, time efficiency, and completion rate for videoconsults compared to telephone consults have been examined previously. Objective: The aim of this study was to determine staff perceptions of the factors that influence implementation, including enablers and barriers, for videoconsults compared to telephone consults, to inform model sustainability. Methods: Semi-structured interviews were conducted with staff (n = 14) involved with the videoconsult service, or who provided care for patients who had a videoconsult. Interviews were coded for positive or negative influence and strength using the Consolidated Framework for Implementation Research (CFIR) 2.0, to understand which constructs influence implementation. Results: Thirty-nine of the 79 constructs, from across four domains were identified as influences for the telephone and videoconsult models. Six constructs were strongly differentiating for videoconsults over telephone consults. Of the 25 positively influencing constructs for the videoconsult model, strongest ratings (+2) were given for innovation advantages, critical incidents, support persons assisting in the consult, financing related to funding reimbursement, and telehealth coordinator capability and motivation. Barriers unique to the videoconsult model included the many steps that were involved, compatibility with workflows, and pharmacist resource. Similarities and differences unique to each model were identified. Conclusion: Findings demonstrated a number of strongly differentiating constructs highlighting superiority of the videoconsult model. However, implementation of both models had multiple enablers and barriers that may influence adoption. The potential of a hybrid service, using both telephone consults and videoconsults, may help optimise delivery of services.